Epidemiology of intrapartum stillbirth and associated factors among women who gave childbirth in Ethiopia: systematic review and meta-analysis - Eskinder Israel; Awoke Abraham; Mihiret Tesfaw; Temesgen Geta; Melkamu Worku Kercho; Samson Dubale; Tagese Yakob; Endale Jambo; Eshetu Elfios (Frontiers Media S.A., 2024)
BackgroundStillbirth always resulted in a multi-dimensional impact from the individual level to the country level at large. It causes psychological depression, social stigmatization, and decreased quality of life for women. Despite several studies conducted in Ethiopia, no national pooled estimates were done. Therefore, this systematic review and meta-analysis sought to assess intrapartum stillbirth and associated factors among women who had childbirth in Ethiopia using the available published evidence.MethodsThe current review included studies conducted in Ethiopia. The databases used primarily were Medline/PubMed, Google Scholar, Scopus, Web of Science, Ethiopian University Repository Online, CINAHL, African Journals Online and Cochrane Library. All cross-sectional studies conducted in English and met eligibility criteria were included in the final review. A random-effects meta-analysis was performed. Data extraction and analysis were also performed using Microsoft Excel and STATA version 14 software respectively.ResultsIn the current review, eleven studies were included, and their quality was assessed before being chosen for the final review. The pooled prevalence of intrapartum stillbirth among women who had childbirth in Ethiopia was 9.21% [95% CI (7.03%, 11.39%); I2 = 90.2, P = 0.000]. Women with a previous history of stillbirth [OR = 5.14, 95% CI (3.53-6.75), I2 = 60.0%, p = 0.04] and had no use of antenatal care {[OR = 0.43, 95% CI (0.18-0.68) I2 = 85.3%, p = 0.001]} were significantly associated with intrapartum stillbirth among women who gave childbirth.ConclusionsNearly one-tenth of women who had childbirth in Ethiopia had an intrapartum SB. Revitalizing the existing health extension package particularly family health services with emphasis on focused antenatal care and counselling as well as with prompt referral system would reduce intrapartum SB. This review calls for the need to assess the quality of ANC provision and tailor targeted interventions to best improve the service quality.